Collaborative Building Design Education Using Building Information Modelling (CodeBIM) : Final Report. - Mills, Julie; Tran, Anh; Parks, Andrea; Macdonald, Jennifer (Office for Learning and Teaching, 2013)
Current building design education practice in Australia rarely involves collaboration between students training for the architecture, engineering and construction (AEC) professions. The construction industry worldwide is moving towards collaborative design practices for the majority of projects, but the AEC education sector is falling behind in this respect. The use of building information modelling (BIM) is widely recognised as having the potential to change the way building projects are run by facilitating collaborative working practices that engage all design team members at an earlier stage in the design process, aided by BIM tools. Graduates with collaborative design skills and BIM expertise will be in high demand and will also have a profound effect on the AEC sector, leading industry change by developing innovative and collaborative working practices using BIM. This is the final report from a project that aimed to address the need for such graduates through the development of a transferable curriculum that can be used by all Australian universities that offer architecture, engineering or construction degrees.